Chronische Nierenerkrankungen – was der Praktiker wissen sollte - Dabers, Thomas; Weckmann, Gesine; Chenot, Jean-Francois; Stracke, Sylvia (DMW - Deutsche Medizinische Wochenschrift, 2017)
Chronic kidney disease (CKD) affects between 3 and 17 % of the population in Europe, especially elderly persons. CKD is a clinical syndrome which may develop in patients with e. g. diabetes mellitus, arterial hypertension or autoimmune diseases. A poorer renal function – especially in old age – is to be considered irrespective of the medication. Many antibiotics and painkillers require dose adjustments. Therapy should be done in a manner which is suitable for indication. Polypharmacy should be avoided as far as possible. Diuretics and RAAS inhibitors are useful drugs in therapy of CKD. Changes of lifestyle are important, so as weight reduction, restriction of salt and fructose, sufficient drinking, strict control of blood glucose, blood pressure and hypercholesterolaemia. Additional acute lesions have to be avoided ("acute-on-chronic renal failure").
Keywords: Chronische Nierenerkrankung; Diuretika; RAAS-Blockade; Schmerzmittel; Lebensstiländerungen